Supplementation of Follicle Stimulating Hormon Into In vitro Maturation Medium to Increase Oocytes Maturation and 4 Cell Stadium Embryo Development of Bligon Goat - Yanuar Achadri; Sigit Bintara; Diah Tri Widayati (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The study was carried out to investigate the effect of follicle stimulating hormon (FSH) into in vitro maturation medium to increase oocytes maturation and 4 cell stadium embryo development of Bligon goat. Goat ovaries were obtained from a slaughterhouse and transported to the laboratory in a flask of NaCl at temperature of 31 – 34°C. Oocytes were aspirated from 2 – 6 mm of follicles into a 3 mL syringe (23G needle) that contained Dulbecco’s Phosphate-Buffered Saline. Oocytes were divided into three groups, i.e tissue culture medium (TCM) with FSH supplementation 0, 50, and 100 IU/mL. Oocytes were put into those medium and incubated on 39°C, 5% CO2, and 95% humidity for 24 hours. Matured oocytes were fertilized with capacitated frozen thawed-semen and incubated on 39°C, 5% CO2, and 95% humidity for 5 hours. Fertilized oocytes were washed for 3 times in TCM and incubated in the same condition for embryo culture. The data of FSH supplementation and embryo development were analyzed using randomized completely one way classification. The results showed that the percentages of mature oocytes from FSH supplementation 0, 50, and 100 IU/mL were 70,48±23,22, 78,48±15,80, and 80,29±12,86%, respectively. Cleavage rate of the two cells stage were 36,00±14,22, 44,00±33,94, and 57,45±31,78%, respectively, and for the 4 cells stage were 27,33±22,04, 35,33±40,73, and 39,45±20,38%. It is concluded that supplementation of FSH in the maturation medium could not increase the percentages of in vitro maturation and embryo development.